REVITALISASI BADAN KOORDINASI WILAYAH (BAKORWIL) PROVINSI JAWA TIMUR DALAM RANGKA EFEKTIFITAS PELAKSANAAN KOORDINASI PEMERINTAHAN DAN PEMBANGUNAN DI DAERAH - Slamet Hari Sutanto; Permadi Setyonagoro; Muhammad Hendra Herdianto (NATAPRAJA, 2019)
The purpose of this study is to develop a policy strategy in strengthening the role and function of the East Java Provincial Coordination Board in the context of the effectiveness of the coordination of the implementation of Government and development in East Java. The research method used is a mixed research approach, with the main analysis technique being the Analytical Hierarchy Process (AHP) method. 40 respondents were selected purposively from all partners related to the implementation of Government and Development in East Java carried out by the Bakorwil. The research was carried out for 6 months, namely between March and August 2018. The research sites were selected from the regencies / cities which were the work areas of the East Java Province Bakorwil which were used as research objects, namely the Pamekasan Bakorwil and Bakjonwil Bojonegoro. The results showed that the chosen policy priority based on the level of interest of the respondents or the most important priority was the information system (0.391), then the second was planning and budgeting (0.320), then the third and fourth priorities were organizational structures (0.144), and supervision function control (0.144), which according to respondents has the same level of importance.